A Note on Lagrangians and Lovelock-Rund’s Identities - Thapa, Gyan Bahadur; López Bonilla, J. (Journal of Institute of Science and Technology, 2015)
Lagrangians and Lovelock-Rund’s identities are important derivations in theory of gravity which is generalization of Einstein's theory of general relativity. In this paper, we construct continuity equations in arbitrary Riemannian 4- spaces, which could be interpreted as conservation laws for the energy and momentum of the gravitational field. We put special attention in general relativity. Journal of Institute of Science and Technology, 2015, 20(2): 136-139